Vascular responses of the spleen to nerve stimulation during normal and reduced blood flow - Greenway, C. V. (1968)
1. The splenic artery flow, the splenic weight and the arterial blood pressure were recorded in cats anaesthetized with sodium pentobarbitone. 2. Oscillations in splenic artery flow and splenic weight were observed. Following occlusion and release of the splenic artery, there was a brief increase in flow to above the pre-occlusion level and the oscillations in flow were greatly increased in amplitude. It is suggested that the brief increase is a consequence of the reduction of arterial pressure and that the oscillations are due to synchronization of rhythmic activity of smooth muscle within the spleen. 3. Stimulation of the splenic nerves resulted in decreases in splenic artery flow and splenic weight. The size of the responses varied with the frequency of stimulation and maximum responses in both flow and weight were obtained at about 3 impulses/sec. 4. After stimulation for 10 min, the splenic weight response was maintained while the flow response showed some recovery towards the control level. 5. When the splenic artery flow was reduced to about half the control level for periods up to 2 hr, the flow and weight responses to stimulation of the splenic nerves remained unchanged; the significance of this after a haemorrhage is discussed. 6. Intravenous administration of atropine or propranolol did not affect the responses to nerve stimulation. After phenoxybenzamine, nerve stimulation caused a smaller decrease in splenic weight, while the splenic artery flow increased to above the control level. This increase was unaffected by atropine but abolished by propranolol.